Enhancing Energy Efficiency and Ethanol Conversion through the Addition of a Heat Exchanger and Reactor in the Catalytic Dehydration Process for Ethylene Production from Ethanol - Kinanti, Agita Ardelia; Febrianti, Hasna Labibah; Dewi, Ni Putu Savitri Mandasari (Journal of Chemical Engineering Research Progress, 2024)
Ethylene production requires high energy costs, and the composition of the ethanol feed is not very pure. The aim of this research is to reduce energy costs slightly while still increasing conversion to obtain a purer ethanol conversion. To achieve this goal, the method used is to add one more heat exchanger and one more reactor. The results obtained turned out that by adding a heat exchanger, we do not need cooling water, but can utilize the output of cryogenic distillation. An energy efficiency of 73.56% obtained and the ethanol conversion obtained was also close to pure with the presence of two reactors with a value of 99.2%. Further process creation is needed to be able to optimize the ethylene production process which is more environmentally friendly, such as making ethylene with bioethanol as feed. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).